Botulinum Toxin A Intradetrusor Injection for Treating Neurogenic Detrusor Overactivity, A Single Centre Experience. Issue 3 (24th October 2013) - MOSLI, Hisham A.; AWAD, Mohannad A.; REZK, Mamdouh M.; ALSABBAN, Abdulrahman E.; TAYIB, Abdulmalik M. S.; ABDULWAHAB, Mohammed H.; ASSIRI, Moayad A.
<x xml:space="preserve">Abstract</x> Objectives To evaluate the efficacy and safety of Botulinum Toxin A (BoNTA) intradetrusor injections in patients with neurogenic detrusor overactivity. Methods All patients provided clinical history and voiding diary, submitted to clinical examination, urine culture; serum creatinine; imaging, including plain abdominal X‐rays, abdomino‐pelvic ultrasonography and voiding cystourethrogram; and urodynamic tests (CMG) . They were managed by intradetrusor injections of BoNTA. For the typical patient, 300 units of BoNTA were injected through 30 injections of 10 u/mL intradetrusally into equally spaced sites of the bladder wall, excluding the trigone, under cystoscopic guidance. Patients were commenced clean intermittent catheterizations (CICs) every 4–6 h post‐injection. Follow up included voiding diaries, abdomino‐pelvic ultrasonography, serum creatinine and CMG, were completed for all patients at 6 and 12 weeks. This study used IBM SPSS Version 20.0 for statistical analysis. Results Forty‐five patients (28 males and 17 females) with a mean age of 19.6 years were subjected to BoNTA intradetrusor injections. A good clinical response (dry patient either completely or more than 50% of the period between CICs) was observed in 68.9 and 66.7% of the patients after 6 and 12 weeks of follow up, respectively. In the group that responded well, the mean bladder volume increased post‐injection by 48.2% and the mean maximum intravesical pressure decreased to 35.3 cm H2O, a 33.4% improvement. No patients had side‐effects related to BoNTA or to the procedure, and no patients experienced a deterioration of their renal functions. Conclusions Intradetrusor BoNTA injections provide a good clinical response. The urodynamic parameters significantly improved in patients with neurogenic detrusor overactivity.